Correlation Between Tumor Suppressor Gene P53 In Some Iraqi Patients With Thyroid Carcinoma By Immunohistochemical Assay and In Situ hybridization Method - Galoub, Abd-Alameer N. (Iraqi Journal of Cancer and Medical Genetics, 2012)
The present study was designed to compare between two methods (Immunohistochemistry and In Situ hybridization ) to investigate the relationshipe between tumor suppressor gene (P53) in some samples of some Iraqi patients with thyroid tissue cancer from different site (papillary, follicular and lymph node). A series of 30 patients with thyroid cancer who had undergone thyroidectomy. All these samples were collected during (2011-2012) . The histologic types included 21 well differentiated papillary , follicular and lymph node carcinomas,and nine poorly differentiated carcinomas.By using Immunohistochemistry , P53 was detected in eighteen out of thirty (60%) , whereas at In Situ hybridization , it was detected in fourteen out of thirty (46.6%), Moreover the positive results of the tumor supprewwor gene (p53) was related in highly significant to each of age, gender, stage and histologic grade of tumor.It is conclude from that immunohistochemistry and in situ hybridization for detection of p53 could be useful in the clinical evaluation of patients with thyroid carcinoma. And suggested that p53 mutations are involved in thyroid carcinogenesis and may play an important role in the malignant transformation of thyroid cancer.